Perlindungan Hukum Para Pihak dalam Transaksi Bisnis Elektronik Online (Postulat, 2023)
Information and communication technology has developed so widely and has a direct impact on providing convenience for people in Indonesia. One of the impacts felt by the community from technological developments can be seen through the increasing number of economic activities that use the internet as a medium for transactions carried out electronically. E-commerce or what is often referred to as electronic transaction is a trading activity carried out online by business actors and consumers in conducting trading activities. Electronic transactions have both good and bad effects on the parties involved. Both consumers and business owners are entitled to legal protection for their losses. This study aims to examine the legal arrangements in electronic business transactions through e-commerce and disclose legal protection for the parties if there is an act of fraud or violation during an electronic business transaction. The problems raised in this study are how the legal protection for the parties in electronic business transactions and what are the legal problems faced by consumers in conducting electronic business transactions. The writing method in this study uses a normative legal analysis method and uses a legal approach related to the rights of the parties, the obligations of the parties, the prohibitions of business actors and the responsibilities of the parties in conducting online transactions. The results of this study indicate that legal protection for parties in electronic business transactions or e-commerce includes legal protection for consumers in the form of: compensation for losses suffered by consumers as regulated in legislation and legal protection for business owners in the form of money advanced by consumers who have entered online transactions. In terms of civil law, legal protection for the parties includes three main principles in making and implementing an agreement, namely a) the principle of freedom of contract or an open system, b) the principle of consensualism, c) the principle of good faith